The effect of word prediction settings (frequency of use) on text input speed in persons with cervical spinal cord injury: a prospective study. Issue 12 (5th June 2017) - Pouplin, Samuel; Roche, Nicolas; Antoine, Jean-Yves; Vaugier, Isabelle; Pottier, Sandra; Figere, Marjorie; Bensmail, Djamel
Abstract: Purpose: To determine whether activation of the frequency of use and automatic learning parameters of word prediction software has an impact on text input speed. Methods: Forty-five participants with cervical spinal cord injury between C4 and C8 Asia A or B accepted to participate to this study. Participants were separated in two groups: a high lesion group for participants with lesion level is at or above C5 Asia AIS A or B and a low lesion group for participants with lesion is between C6 and C8 Asia AIS A or B. A single evaluation session was carried out for each participant. Text input speed was evaluated during three copying tasks: without word prediction software (WITHOUT condition) with automatic learning of words and frequency of use deactivated (NOT_ACTIV condition) with automatic learning of words and frequency of use activated (ACTIV condition) Results: Text input speed was significantly higher in the WITHOUT than the NOT_ACTIV ( p < 0.001) or ACTIV conditions ( p = 0.02) for participants with low lesions. Text input speed was significantly higher in the ACTIV than in the NOT_ACTIV ( p = 0.002) or WITHOUT ( p < 0.001) conditions for participants with high lesions. Conclusions: Use of word prediction software with the activation of frequency of use and automatic learning increased text input speed in participants with high-level tetraplegia. For participants with low-level tetraplegia, the use of word prediction software with frequency of use and automatic learning activated only decreased the number of errors. Implications in rehabilitation: Access to technology can be difficult for persons with disabilities such as cervical spinal cord injury (SCI). Several methods have been developed to increase text input speed such as word prediction software.This study show that parameter of word prediction software (frequency of use) affected text input speed in persons with cervical SCI and differed according to the level of the lesion. For persons with high-level lesion, our results suggest that this parameter must be activated so that text input speed is increased. For persons with low lesion group, this parameter must be activated so that the numbers of errors are decreased. In all cases, the activation of the parameter of frequency of use is essential in order to improve the efficiency of the word prediction software. Health-related professionals should use these results in their clinical practice for better results and therefore better patients 'satisfaction.